Evaluation of the effect of sodium fluoride addition on some mechanical properties of heat cure acrylic denture base materials - AM, Ali (Journal of Baghdad College of Dentistry, 2014)
Background: The geriatric patients wearing removable partial dentures are increasing in proportion. At the same time, the root caries prevalence accompanied by gingival recession is increasing. A variety of vehicles can deliver fluoride into the oral cavity, including fluoride mouth-rinse, fluoride dentifrice, topical fluoride, and fluoride-releasing restorative materials, all of which effectively prevent root caries and suppress recurrent caries. This study aimed to evaluate the effect of sodium fluoride addition on some mechanical properties of heat cure acrylic denture base material. Material and method: A total of 90 samples were prepared in this study, then divided into three main groups according to the type of test used (hardness, tensile and transverse strength tests). Each main group was subdivided into three main subdivisions according to percentage of sodium fluoride addition to the heat cure acrylic denture base material (control no addition, 2%NaF ,and 5%NaF sodium fluoride groups) Results: The sodium fluoride addition to acrylic denture base materials showed slight but non significant increase in transverse strength and tensile strength tests while the results showed significant and highly significant differences for 2%NaF and for 5%NaF shore D hardness groups respectively. Conclusions: Addition of 2% and 5% sodium fluoride to heat cure acrylic resin is considered advantageous as the mechanical properties of resin denture base materials in respect to hardness tensile and transverse strength were not adversely affected.